Modular design workflow for 3D printable bioresorbable patient-specific bone scaffolds: extended features and clinical validation - Herath, Buddhi; Laubach, Markus; Suresh, Sinduja; Schmutz, Beat; Little, J. Paige; Yarlagadda, Prasad K. D. V.; Delbrück, Heide; Hildebrand, Frank; Hutmacher, Dietmar W.; Wille, Marie-Luise (Frontiers in Bioengineering and Biotechnology, 2024)
A previously in-house developed patient-specific scaffold design workflow was extended with new features to overcome several limitations and to broaden its adaptability to diverse bone defects, thereby enhancing its fit for routine clinical use. It was applied to three clinical cases for further validation. A virtual surgical resection tool was developed to remove regions of the bone defect models. The minor cavity fill module enabled the generation of scaffold designs with smooth external surfaces and the segmental defect fill module allowed a versatile method to fill a segmental defect cavity. The boundary representation method based surgical approach module in the original workflow was redeveloped to use functional representation, eliminating previously seen resolution dependant artefacts. Lastly, a method to overlay the scaffold designs on computer tomography images of the defect for design verification by the surgeon was introduced. The extended workflow was applied to two ongoing clinical case studies of a complex bilateral femoral defect and a humerus defect, and also to a case of a large volume craniomaxillofacial defect. It was able to successful generate scaffolds without any obstructions to their surgical insertion which was verified by digital examination as well as using physical 3D printed models. All produced surface meshes were free from 3D printing mesh errors. The scaffolds designed for the ongoing cases were 3D printed and successfully surgically implanted, providing confidence in the extended modular workflow’s ability to be applied to a broad range of diverse clinical cases.